Perlindungan Hukum Terhadap Penggunaan Suara Penyanyi dalam Pembuatan Karya Seni Musik Menggunakan Kecerdasan Buatan - Wear, Elsa Amalia; Berlianty, Teng; Narwadan, Theresia Nolda Agnes (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2024)
Currently, there are many musical works of art that are sung by artificial intelligence using the voice of a particular singer. Where, the singer's voice is taken through a music recording and then inputted, studied, and replicated by artificial intelligence. Of course, the taking and use of the singer's voice is done without the permission and rights of the relevant parties. In fact, Law Number 28 of 2014 concerning Copyright has guaranteed the rights of singers as one of the relevant rights holders. The research method used is normative juridical using a statutory approach and conceptual approach. The legal sources used are primary, secondary, and tertiary legal materials with legal material collection techniques using literature study techniques analyzed with qualitative descriptive techniques. The results showed that legal protection of singers whose voices are used in the creation of musical works of art through the use of artificial intelligence technology can be provided in terms of prevention through registration of creations, supervision by the government, and through the procurement of binding legal products. As well as repressive legal protection by blocking and closing content or access rights, filing lawsuits to the Commercial Court, and imposing criminal sanctions.